2017
DOI: 10.1007/s12565-017-0422-x
|View full text |Cite
|
Sign up to set email alerts
|

The malaris muscle: its morphological significance for sustaining the intraorbital structures

Abstract: The orbicularis oculi muscle, an important mimetic muscle, was investigated to ascertain its anatomical relation to facial aging-especially its orbital part (Oo). Previous studies of the distinct muscle bundles frequently found inferior to the Oo have provided various definitions, including that of the malaris muscle. This study aimed to examine these muscle bundles and clarify their function in facial aging. Twelve heads of Japanese cadavers (average age: 82.5 years old) were dissected to observe the muscles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…It is apparent that in general the malaris muscle is currently perceived comprising the lateral muscle bundle inclining downwards medially [2141519], the medial muscle bundle inclining downwards laterally mentioned in the studies of Henle [10] and Lightoller [11]. The suspending bundle has not been mentioned until the latest study of Kampan et al [16].…”
Section: Anatomical Concept Of Malaris Musclementioning
confidence: 99%
See 4 more Smart Citations
“…It is apparent that in general the malaris muscle is currently perceived comprising the lateral muscle bundle inclining downwards medially [2141519], the medial muscle bundle inclining downwards laterally mentioned in the studies of Henle [10] and Lightoller [11]. The suspending bundle has not been mentioned until the latest study of Kampan et al [16].…”
Section: Anatomical Concept Of Malaris Musclementioning
confidence: 99%
“…The detail of the medial bundle is scarce, however the studies that revealed the anatomical description of the medial bundle exist [101116]. The medial bundle of the malaris muscle was described as the muscle bundle adhering medially to the orbital part of the orbicularis oculi muscle and running downwards laterally.…”
Section: Attachment Sitesmentioning
confidence: 99%
See 3 more Smart Citations